The re-making of Europe: The long view. (February 2020) - Room, Graham
This article starts with three commonplace judgements on the European Union – its success in healing the wounds of war, its failure to win democratic engagement and its vulnerability now to the seeds of disintegration. Setting these against the background of the High Middle Ages, and the original making of Europe, the article argues that each of these judgements is overly simplistic and for reasons that are closely interconnected. They are, moreover, the 'high politics' of European integration, expressing the concerns of political elites. Against these, the article proposes a rather different agenda, in relation to the following: social and economic justice; the turmoil, dislocation and hurt that European integration produces; the critical questioning of political elites; and the creative diversity of the Union. These are the 'hot politics' that matter to ordinary citizens.